Analisis kandungan standard profesionalisme keguruan : cadangan implimentasi standard keguruan Pendidikan Islam berasaskan ‘RIADHAH RUHIYYAH’ - Habibah @ Artini Ramlie; Norshahrul Marzuki bin Mohd. Nor; Zaharah Hussin (2020)
This study is an analysis of the contents of the teacher standards in Malaysia and several other countries. The objective of the study was to examine the contents of these teacher standards and propose an Islamic Education Teacher Professionalism Model based on ‘Riadhah Ruhiyyah’ as one of the elements in the teacher standards in Malaysia. This study utilised the content analysis method with the Standard Guru Malaysia (SGM) document and various teacher standards from other countries which were accessed online as instruments in the study. From this review, Islamic Education teacher standards centred on the Islamic Education Teacher Professionalism Model based on ‘Riadhah Ruhiyyah’ were ascertained as viable elements to be incorporated into the teacher standards in Malaysia.